2016
DOI: 10.1158/1078-0432.ccr-15-2780
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Limits Secretion of Lumican by Activated Stellate Cells within Primary Pancreatic Adenocarcinoma Tumors

Abstract: Purpose Pancreatic ductal adenocarcinoma (PDAC) is lethal cancer whose primary tumor is characterized by dense composition of cancer cells, stromal cells and extracellular matrix (ECM) composed largely of collagen. Within the PDAC tumor microenvironment, activated pancreatic stellate cells (PSC) are the dominant stromal cell type and responsible for collagen deposition. Lumican is a secreted proteoglycan that regulates collagen fibril assembly. We have previously identified that the presence of lumican in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…As illustrated in Fig. 1a, positive HIF1α staining was seen in the stroma and the epithelial compartments, suggesting hypoxic conditions within the TME; lumican protein was primarily located in stromal compartment, a finding consistent with our previous studies which showed that activated pancreatic stellate cells in the tumor are a principal source of stromal lumican [14,15]. Importantly, lumican and HIF1α expression were observed within the same microscopic regions within tumor stromal compartment, suggesting lumican expression and secretion occurs within hypoxic regions of the TME.…”
Section: Hypoxia Reduces Lumican Expression and Secretion By Pancreatsupporting
confidence: 91%
See 1 more Smart Citation
“…As illustrated in Fig. 1a, positive HIF1α staining was seen in the stroma and the epithelial compartments, suggesting hypoxic conditions within the TME; lumican protein was primarily located in stromal compartment, a finding consistent with our previous studies which showed that activated pancreatic stellate cells in the tumor are a principal source of stromal lumican [14,15]. Importantly, lumican and HIF1α expression were observed within the same microscopic regions within tumor stromal compartment, suggesting lumican expression and secretion occurs within hypoxic regions of the TME.…”
Section: Hypoxia Reduces Lumican Expression and Secretion By Pancreatsupporting
confidence: 91%
“…A growing body of literature has identified lumican as an inhibitor of multiple hallmarks Edited by G. Del Sal characteristics of cancer biology including: cancer cell proliferation, invasion and metastasis as well as tumor growth promoting inflammation and angiogenesis [8][9][10][11][12][13]. Our laboratory has observed that activated pancreatic stellate cells within the tumor microenvironment (TME) are a principal source of stromal lumican [14,15], and mounting evidence suggests lumican is also a key regulator of ECM and ECM-cell interactions within the TME [16].…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Our recent work demonstrated that activated pancreatic stellate cells within the tumour are a principle source of stromal lumican and the presence of lumican within the stroma of primary PDAC tumours is associated with decreased metastasis and prolonged survival. 10,13 Based on these results, we investigated whether the absence of host lumican would influence PDAC growth (Figure 1a, upper-right). Using a syngeneic orthotopic pancreatic tumour model, we compared growth of PanO2 cells within the pancreas of wild-type C57B6 mice versus those with loss of one or both copies of the LUM gene.…”
Section: Resultsmentioning
confidence: 99%
“…Paraffin embedded tumor tissues were cut into 5 µm sections. Immunohistochemistry or immunofluorescence staining was performed using the methods described previously (18). Images were captured with an Olympus DP72 camera and CellSens software (Center Valley, PA) on an Olympus BX51 microscope.…”
Section: Methodsmentioning
confidence: 99%